Relationship of the SITLESS intervention on medication use in community-dwelling older adults: an exploratory study - Ruben Viegas; Filipa Alves da Costa; Filipa Alves da Costa; Romeu Mendes; Romeu Mendes; Manuela Deidda; Emma McIntosh; Oriol Sansano-Nadal; Oriol Sansano-Nadal; Juan Carlos Magaña; Dietrich Rothenbacher; Michael Denkinger; et al. (Frontiers Media S.A., 2023)
BackgroundSedentary behavior (SB) and physical activity (PA) interventions in older adults can improve health outcomes. Problems related with aging include prevalent comorbidity, multiple non-communicable diseases, complaints, and resulting polypharmacy. This manuscript examines the relationship between an intervention aiming at reducing SB on medication patterns.MethodThis manuscript presents a local sub-analysis of the SITLESS trial data on medication use. SITLESS was an exercise referral scheme (ERS) enhanced by self-management strategies (SMS) to reduce SB in community-dwelling older adults. We analyzed data from the ERS + SMS, ERS and usual care (UC) groups. Patient medication records were available at baseline and at the end of the intervention (4-month period) and were analyzed to explore the effect of SITLESS on medication patterns of use.ResultA sample of 75 participants was analyzed, mostly older overweight women with poor body composition scores and mobility limitations. There was a significant reduction of 1.6 medicines (SD = 2.7) in the ERS group (p < 0.01), but not in the UC or ERS + SMS groups. Differences were more evident in medicines used for short periods of time.ConclusionThe findings suggest that an exercise-based program enhanced by SMS to reduce SB might influence medication use for acute conditions but there is a need to further investigate effects on long-term medicine use in older adults.